Case Report: A successful multidisciplinary approach to doxorubicin extravasation from a PICC-port in a patient with breast cancer - Calabrò, Concetta; Iacovelli, Serena; De Palma, Giuseppe; Carravetta, Giuseppe; Garofalo, Domenica; Giotta, Francesco; Latorre, Agnese; Nardulli, Patrizia; Ressa, Cosmo Maurizio; Vitale, Elsa; De Santis, Valerio; Mastrandrea, Giovanni (Frontiers in Oncology, 2025)
BackgroundInfusion of chemotherapy drugs through central venous catheters in the bloodstream facilitates direct access to disseminated cancer sites to interrupt the growth and/or spread of abnormal cells. To represent the significance of a rapid, multidisciplinary intervention codified by a hospital-adopted procedure for the treatment of this specific type of extravasation.MethodsA case of a 63-year-old female patient with no comorbidities but overweight who was admitted to our hospital in 2023 was discussed. The oncologist requested the placement of a long-term central venous access for chemotherapy, expected to last at least 5–6 months. This case report describes a massive anthracycline extravasation through a PICC-port. Such a serious complication requires not only the prompt administration of dexrazoxane but, more importantly, a multidisciplinary approach. Without comprehensive and timely intervention, the patient would have likely lost the upper limb.Clinical implicationsFollowing the surgical and pharmacological treatment, the patient achieved a restoration of normal limb function, thus resuming all regular activities. This outcome was made possible primarily due to the timely and professional intervention of the multidisciplinary team, which minimized the severe complications that doxorubicin extravasation can cause. Tunneling of the catheter, which moves the extravasation site (port pocket) away from the venipuncture site, is equally important. Another noteworthy element is the resumption of chemotherapy treatment, which might have been interrupted due to the severe complication resulting from the extravasation.